Mobilité de l'arsenic dans les sédiments de lacs subarctiques contaminés par l'activité minière - Leclerc, Émilie (Université Laval, 2021)
The goal of this thesis is to quantify the diagenesis of arsenic (As) in the sediments, using them as environmental archives and identify the key reactions of As. Eight lakes have been visited in June 2018 and May 2019, along an 80 km transect northwest from the gold mine Giant, near Yellowknife in the Northwest Territories, Canada to collect surface water, sediment cores and porewater. These samples have been analyzed to obtain the dissolved and solid concentration of organic carbon, As, iron (Fe), manganese (Mn) and aluminium (Al) and anions (nitrate, sulfate, sulfide and chloride). As concentrations in porewater were interpreted using inverse diagenetic modeling and thermodynamics calculations. The history of the fluxes of solid As deposited at the bottom of the lakes was calculated after correction for the influence of diagenesis. Diffusive fluxes of As at the sediment-water interface in response to contamination from mining activity were calculated for the two years of sampling. The results show that diagenesis is greater in lakes with lower sedimentation rates. After correction, the data indicates that the maximum As fluxes coincide with the period of mine activity. Nonetheless, lakes near the mine are still influenced by large inputs of dissolved As from their watersheds, and show high diffusive fluxes of As to the water column. Thermodynamic calculations of speciation and saturation index suggest that the mobility of Asis related to that of iron oxides and sulfur. Amorphous iron sulfide forms in the sediment and As coprecipitates or adsorbs to this mineral phase. Finally, the timing of the melting of the ice cover, which allows the arrival of oxygen, seems to determine the mobility of As in the spring. In the context of climate change shortening the duration of ice cover, an in-depth study of the effect of ice cover on redox conditions is desirable. L’objectif de ce mémoire est de quantifier la diagenèse de l’arsenic (As) dans les sédiments, d'utiliser ceux-ci comme archive environnementale et ...